Aprendizaje musical significativo - Gabriel Rusinek (Ediciones Complutense, 2004)
Understanding the meaningfulness of music learning requires two complementary perspectives. On the one hand, I maintain that the declarative knowledge about music is meaningful when it is related in a non trivial manner to the musical event it denotes, and propose a way of evaluating that meaningfulness through tests that demand the use of different processes of the auditive cognition. On the other hand, given that it is the apprentice who decides to build that relation between musical concept and musical experience, I argue that we need to understand his or her motivations, and propose the use of qualitative research techniques to interpret the meanings attributed to the learning procedures lived in the classroom.